2019
DOI: 10.1101/19006809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasminogenuria is associated with podocyte injury, edema, and kidney dysfunction in incident glomerular disease

Abstract: Urinary plasminogen/plasmin, or plasmin(ogen)uria, has been demonstrated in proteinuric patients and exposure of cultured podocytes to plasminogen results in injury via oxidative stress pathways. A causative role for plasmin(ogen) as a “second hit” in kidney disease progression has yet to be demonstrated in vivo, and the association between plasmin(ogen)uria and kidney function in glomerular diseases remains unclear. We performed comparative studies in a puromycin aminonucleoside (PAN) nephropathy rat model tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
(151 reference statements)
0
3
0
Order By: Relevance
“…In C-PROBE, participants were enrolled between 2009 and 2016. Full details of these cohorts were previously published (39,40). For validation cohorts, we defined the presence or absence of AIN based on official biopsy interpretations.…”
Section: Methodsmentioning
confidence: 99%
“…In C-PROBE, participants were enrolled between 2009 and 2016. Full details of these cohorts were previously published (39,40). For validation cohorts, we defined the presence or absence of AIN based on official biopsy interpretations.…”
Section: Methodsmentioning
confidence: 99%
“…Podocytes play a pivotal role in the maintenance of the glomerular filtration barrier, whereas podocyte injury usually results in proteinuria and detachment from the human glomerular basement membrane (3,4). Current studies Original Article on the biology and gene disruption of podocytes have indicated the causal relationship between abnormalities of podocytes and proteinuria and glomerulosclerosis (4)(5)(6). Over the decades, a number of glomerular responses to podocyte dysfunction have been determined, which has helped to decode the complex scenario of podocyte injury and the resultant consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we and other investigators have explored potential therapeutics for podocyte injury and the underlying molecular mechanisms (1,7,8). For example, Egerman and colleagues recently verified the role of plasmin-induced podocyte injury in the puromycin aminonucleoside (PAN) nephropathy model, and have demonstrated that amiloride also has podocyteprotective properties (5). Chen et al verified that hydrogen sulfide (H 2 S) confers a protective effect against TNFα-induced neuronal cell apoptosis via miR-485-5p and type 1-associated DEATH domain protein (TRADD) signaling (9).…”
Section: Introductionmentioning
confidence: 99%